Neointimal characteristic changes following drug-coated balloons in lesions with repeated revascularization - Yosuke Takei; Hiroyoshi Mori; Takahiro Tezuka; Ayumi Omura; Daisuke Wada; Hiromoto Sone; Kazuma Tashiro; Masahiro Sasai; Tokutada Sato; Hiroshi Suzuki (Therapeutic Advances in Cardiovascular Disease, 2023)
Background: Since their emergence, drug-coated balloons (DCBs) have been used widely to treat in-stent lesions with coronary artery disease (CAD). However, despite their superior efficacy to balloon angioplasty, how DCBs affect neointimal characteristics is poorly understood. Objectives: We aimed to assess the neointimal characteristic changes following DCB treatment. Methods: Using optical frequency domain imaging (OFDI), we serially observed the in-stent lesion site just after and 1 year after DCB angioplasty in 12 lesions of 11 patients with repeated revascularization. Neoatherosclerosis was defined as lipid-laden neointima with or without calcification in the stented lesion. Progression or regression of neoatherosclerosis, newly formed neointimal calcification, newly formed uncovered strut and newly formed evagination were assessed. Tiny tissue protrusion was also recorded as mushroom-like protrusion. Results: Underlying stents were first-generation ( n  = 5) or newer ( n  = 7) drug-eluting stents (DESs) with implantation durations ranging from 1 to 15 years (median 8 years). Surprisingly, two-thirds of the lesions (67%, 8 of 12) showed progression of neoatherosclerosis, while a quarter of lesions (25%, 3 of 12) showed regression of neoatherosclerosis. The maximal lipid arc increased from 122° to 174°. Newly formed neointimal calcification was observed in 2 of 12 lesions (16%). Newly formed uncovered struts (33%; 4 of 12) and newly formed evaginations (33%; 4 of 12) were not rare. Mushroom-like protrusion was found in a quarter of lesions (25%; 3 of 12). Conclusion: Our study demonstrated that a considerable number of lesions showed varied neointimal characteristic changes in a small number of patients. Further studies in a larger population are needed to understand the clinical impact of these findings.